COMBUSTION ANALYSIS OF D-LIMONENE AS AN ADDITIVE TO DIESEL-BIODIESEL BLENDS IN COMPRESSION IGNITION ENGINES - Micheli, L. F.; Pereira, L. E. R.; Módolo, D. L.; Saruhashi, W. K. D. C. (Revista de Engenharia Térmica, 2019)
Vegetable oils, when subjected to transesterification process generate “vegetable oils esters”, with similar properties as density, cetane number, heating values, air-fuel ratio. However, problems resulting from the higher viscosity, leads to a worst spraying and combustion, formation of undesirable deposits on engine parts and contamination of the lubricant oil. Due to these problems, it is interesting to study an additive, also derived from biomass, to improve the characteristics of biodiesel for a suitable use in diesel engines. This paper proposes an additive (d-limonene obtained from orange peel) and preliminary results obtained from the tests in a stationary diesel engine fueled with mixtures of diesel/biodiesel/d-limonene, in different concentration to compare with a regular diesel-biodiesel blend and analyzes the influence of the additive on the combustion process. The diesel oil used was purchased from BR supply network (containing 7% biodiesel in its composition) and two blends with different concentrations of the additive (1% and 3% of d-limonene) were prepared and tested. Diesel without additive was also tested. The effects of the DS10 addititivation with d-limonene in the combustion process of a diesel engine have been analyzed, the results obtained were satisfactory showing the positive effects in the combustion process with the addition of d-limonene in diesel-biodiesel blends, decreasing the ignition delay around 2 degrees and showing an improvement in the cetane number of the fuel.